The Impact of Staying at Home on Controlling the Spread of COVID -19: Strategy of Control - Zakary, Omar; Bidah, Sara; Rachik, Mostafa (Revista Mexicana de Ingenieria Biomedica, 2020)
In this paper, we present a new mathematical model to describe the evolution of the COVID-19 in a population. We aim to investigate an optimal strategy of control to bring the situation under control in Italy and Morocco, where the COVID-19 pandemic is sweeping country after country. The Italian and Moroccan authorities have declared a state of emergency in response to the growing threat of this novel coronavirus (COVID-19) outbreak by March 09 and 20, respectively. The state of emergency means that citizens cannot go out to public spaces without special authorization from local authorities. But after all these efforts exerted by these authorities, the number of new cases of the COVID-19 continues to rise significantly, which confirms the lack of commitment of some citizens. The first objective of this article is to estimate the number of these people who underestimate the lives and safety of citizens and put them at risk. To do this, we use real data of the COVID-19 in Italy and Morocco to estimate the parameters of the model, and then we predict the number of these populations. After that, we investigate an optimal control strategy that could be the optimal and efficient way for the Moroccan authorities and other countries to control the spread of the COVID-19 based on the Italian experience. Numerical examples are provided to illustrate the efficiency of the strategy of control that we propose.